Hepatoprotective Activity of Vitamin E and Metallothionein in Cadmium-Induced Liver Injury in Ctenopharyngodon idellus. (11th April 2018) - Duan, Yajiao; Duan, Jing; Feng, Yang; Huang, Xiaoli; Fan, Wei; Wang, Kaiyu; Ouyang, Ping; Deng, Yongqiang; Du, Zongjun; Chen, Defang; Geng, Yi; Yang, Shiyong
Abstract : As an environmental and industrial pollutant, cadmium (Cd) can cause a broad spectrum of toxicological effects. Multiple organs, especially the liver, are considerably affected by Cd in both humans and animals. We investigated the protective effects of metallothionein (MT) and vitamin E (VE) supplementation on Cd-induced apoptosis in the grass carp ( Ctenopharyngodon idellus ) liver. Grass carp were divided into four groups: the control group, Cd + phosphate-buffered saline (PBS) group, Cd + VE group, and Cd + MT group. All fish were injected with CdCl2 on the first day and then VE, MT, and PBS were given 4 days postinjection, respectively. The results showed that Cd administration resulted in liver poisoning in grass carp, which was expressed as an increase in Cd contents, malondialdehyde (MDA) concentration, percentage of hepatocyte apoptosis, and apoptosis-related gene mRNA transcript expression. However, VE and MT treatments protected against Cd-induced hepatotoxicity in grass carp by decreasing Cd contents, lipid peroxidation, and histological damage and reducing the percentage of hepatocyte apoptosis by regulating related mRNA transcript expression. These data demonstrate that oxidative stress and activation of the caspase signaling cascade play a critical role in Cd-induced hepatotoxicity. However, VE and MT alleviate Cd-induced hepatotoxicity through their antioxidative and antiapoptotic effects, and MT has a more powerful effect than VE.